Basic and applied salt mechanics : proceedings of the 5th Conference on Mechanical Behaviour of Salt, Bucharest, 9-11 August 1999 /: proceedings of the 5th Conference on Mechanical Behaviour of Salt, Bucharest, 9-11 August 1999. (2020) - Unknown
No abstract available